Analisis Efisiensi Saluran Pemasaran Gula Aren - Siti Mutia Septina (Ma'soem University, 2023)
This study aims to determine the marketing channel of palm sugar, the amount of cost, margin, and profit of palm sugar marketing, and the most efficient marketing channel based on the percentage of cost of total production value. The sampling technique was carried out by the Census method, while for the sample of marketing institutions was taken by Snowball Sampling and obtained 5 collecting traders and 5 retailers. The data analysis was carried out descriptively. The results showed that there were two sugar marketing channels in Cibungur Village, Rancakalong District, Sumedang Regency. In marketing channel one only involves one marketing institution, namely retailers, while marketing channel two involves two marketing institutions, namely collecting traders and retailers. Marketing efficiency at retailers in channel one amounted to 1.47%. Marketing efficiency at the collector traders in channel two amounted to 8.09%, while at the retailer traders amounted to 1.42%. Thus all traders have efficient channels because they have an efficiency value of less than 50%, and the most efficient channel is obtained at retailers in channel two with an efficiency value of 1.42%, this shows the smallest marketing costs (efficient).